The Influence of Investors’ Personality on Decision Making in the Secondary Equity Market – Big Five Personality Model - Isidore, Renu; Arun, C Joe (The Economics and Finance Letters, 2022)
Decision-making in an unfamiliar environment like the stock market is a difficult task, particularly given the immense amount of information and peer pressure. This study aims to analyze the influence of investors’ personality, assessed using the Big Five personality model, on investors’ decision-making in the Indian secondary equity market. Indian secondary equity investors in the city of Chennai were selected as the study population, and data was gathered from a sample of 436 investors using the questionnaire survey method. A Pearson correlation analysis was conducted to study the relationships between investors’ decision-making tools and personality dimensions, and significant correlation relationships were identified. Multiple linear regression was then used to analyze the linear relationship between the returns earned from equity investment and the personality dimensions and decision-making tools, as well as several demographics and financials. The results of the study could help investors better understand their equity decision-making in terms of the influence of their personality and guide them to adopt appropriate decision-making tools to increase their equity returns. Financial advisors could also benefit from this study as it would allow them to correlate their clients’ personalities and decision-making tools and suggest the most appropriate investment strategies.